2021
DOI: 10.1186/s13044-021-00101-5
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hemiagenesis with a TI-RADS 2 nodule in the contralateral lobe

Abstract: Background Thyroid hemiagenesis is a rare congenital anomaly in which one lobe of the thyroid gland fails to develop. There is an increased incidence of associated thyroid disorders in patients with thyroid hemiagenesis. Case presentation A 32-year-old Ugandan woman presented with a complaint of painless neck swelling of 3-months duration. The swelling was associated with a globus sensation. There was no history of thyroid – related problems or tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…The aetiology of THA remains unknown, but the defect may be due to the failure of the thyroid to become a bi-lobed structure and spread laterally 2. THA occurs as sporadic but familial clustering has been reported earlier 17. Thyroid transcription factors—TTF1 (NKX2), PAX and TTF2 (FOXE1) have been associated with THA 8 11 17.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of THA remains unknown, but the defect may be due to the failure of the thyroid to become a bi-lobed structure and spread laterally 2. THA occurs as sporadic but familial clustering has been reported earlier 17. Thyroid transcription factors—TTF1 (NKX2), PAX and TTF2 (FOXE1) have been associated with THA 8 11 17.…”
Section: Discussionmentioning
confidence: 99%
“…the presence of thyroglossal cysts) are more common compared to the absence of either lobe which is quite rare [ 25 ]. The cause of THA is not known and possible theories include failure of descent, defects in lobulation, or genetic aberrations [ 4 ].…”
Section: Reviewmentioning
confidence: 99%
“…Different studies have shown that in 80% of cases, it affects the left lobe with an L:R ratio of 4:1. The absence of the isthmus is seen in 50% of cases with hemiagenesis of the left lobe while the absence of the right lobe is seen mostly with agenesis of the isthmus [ 4 ]. Frequently, THA is an incidental phenomenon as the majority of patients have normal thyroid function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid hemiagenesis (THA) is an inborn absence of one thyroid lobe of largely unknown etiopathogenesis, affecting 0.05–0.5% of the population [ 2 ]. The anomaly rarely causes CH, thus may remain undetected until adulthood [ 3 , 4 ]. However, it has been demonstrated to pose an increased risk of thyroid compensatory enlargement, nodular goiter, and possibly also autoimmune thyroid diseases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%